(untitled) (International Journal of Innovative Technologies in Economy, 2022)
Critical infrastructures (include the body of systems, networks, and assets that are so essential that their continued operation is required to ensure the security of a given nation, its economy, and the public’s health and/or safety) are significant for the growth and development of our society, drastically affecting most of the everyday activities as the components of the critical infrastructures are increasingly vulnerable to a dangerous mix of traditional and nontraditional types of threats. Taking into account a significant role of Critical Infrastructure in national and international security maintenance, the article analyses and interprets the policy pillars of Critical Infrastructure concepts in the European Union, NATO as well as in G7 Countries. Particular attention is paid to determining the functional purpose, approaches to the classification of the main components of critical infrastructure (structural content) and characteristics of them. At the end of this article there is suggested a generalized view regarding to the essence of Critical Infrastructure, as well as attention is drawn to the fact that the adopted approaches generally take into account that Critical Infrastructure now rarely exist or function in isolation, rather, they are becoming more tightly coupled, interconnected and interacted that creates a complex multisystem - a system-of-systems.